2011
DOI: 10.1073/pnas.1013928108
|View full text |Cite
|
Sign up to set email alerts
|

Functional specialization for auditory–spatial processing in the occipital cortex of congenitally blind humans

Abstract: The study of the congenitally blind (CB) represents a unique opportunity to explore experience-dependant plasticity in a sensory region deprived of its natural inputs since birth. Although several studies have shown occipital regions of CB to be involved in nonvisual processing, whether the functional organization of the visual cortex observed in sighted individuals (SI) is maintained in the rewired occipital regions of the blind has only been recently investigated. In the present functional MRI study, we comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
243
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(276 citation statements)
references
References 54 publications
22
243
2
3
Order By: Relevance
“…The maximum volume level of the auditory stimuli was adjusted so that their intensity was the same across conditions. In addition, the intensity of the auditory stimuli was individually adjusted inside the scanner and before testing to equalize the perceived loudness across participants (Collignon et al, 2011Moerel et al, 2012Moerel et al, , 2013. This was done by increasing or decreasing the intensity of the auditory stimuli until a hearing level was reached that was both audible and comfortable for each participant.…”
Section: Stimulimentioning
confidence: 99%
“…The maximum volume level of the auditory stimuli was adjusted so that their intensity was the same across conditions. In addition, the intensity of the auditory stimuli was individually adjusted inside the scanner and before testing to equalize the perceived loudness across participants (Collignon et al, 2011Moerel et al, 2012Moerel et al, , 2013. This was done by increasing or decreasing the intensity of the auditory stimuli until a hearing level was reached that was both audible and comfortable for each participant.…”
Section: Stimulimentioning
confidence: 99%
“…The right dorsal occipital lobe in particular is known to be prominently active when blind but not sighted individuals localize sounds (Collignon, Lassonde, Lepore, Bastien, & Veraart, 2007;Collignon, Vandewalle et al, 2011;Renier et al, 2010;Weeks et al, 2000), and it is interesting to note that both EB and LB showed strong activation of this region when lateralized objects were being discerned through echoes (Figures 5 and S4), but that this area was not activated by either EB or CB when there was no variation in object location (i.e., the Shape and Material task of Experiment 1).…”
Section: Other Echolocatorsmentioning
confidence: 99%
“…A secondary question that the topic of feature-specific activation in the blind raises relates to the broader issue in sensory substitution literature concerning how the occipital lobe is colonized by non-visual sensory input, once it is deprived of visual input as occurs in the blind (c.f., Collignon, Vandewalle et al, 2011). Converging evidence indicates that the age of onset of visual deprivation affects the degree of functional as well as structural brain reorganization that occurs within occipital cortex, with the largest amount of reorganization occurring when sight loss coincides with sensitive periods of neurodevelopment (for a review, see Noppeney, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The metabolic demand of the occipital cortical areas of blind humans is elevated compared with sighted humans (Wanet-Defalque et al, 1988;Veraart et al, 1990;De Volder et al, 1997). Moreover, the neural activity levels that are present in these regions are modulated by other sensory modalities and are proposed to contribute to higher cognitive capacities such as language and episodic memory (Sadato et al, 1996;Cohen et al, 1997;Büchel et al, 1998;Röder et al, 1999Röder et al, , 2002Bavelier and Neville, 2002;Amedi et al, , 2004Burton, 2003;Gougoux et al, 2005;Raz et al, 2005;Collignon et al, 2009Collignon et al, , 2011Merabet and Pascual-Leone, 2010;Bedny et al, 2011;Schepers et al, 2012).…”
Section: Introductionmentioning
confidence: 99%